Proposed Social Media Strategy for PT. Merpati Nusantara Airlines - Mandagi, Marcia Louise; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2014)
Abstract- Growth phenomenon of the number of internet users in Indonesia has reached 55 million people; it is driven by the growth of population which raises the need of digital technology. Social Media becomes a favorite activity in internet usage. Based on city research, Twitter is the most accessed among two cities, which are Jakarta and Bandung. In Indonesia, the number of twitter account owners almost reaches 30 million. Nowadays, Social Media is an instrument that can be used for Marketing Communications. For brand holders, Social Media is not only defined as the sharing of information and communication, but also often used as a weapon for branding. Merpati Nusantara is one company in airlines industry in Indonesia that used social media. Through Social Media usage, companies can enter the consumersâ€™ mind easier. By using social media, Merpati Nusantara facilitates direct communication with their consumers and gains many inputs or suggestions that come from the consumers. Building awareness toward consumers becomes a crucial thing for the brand. In this case, Social Media plays an important role as a way for the company to communicate with its customers. Purpose of this study that Merpati Nusantara to further strengthen its role in social media strategy and supported by the creation of an Brand Ecosystem in the company and adopt a new model of Customer Social Context and Social Contagion that strategy is made according to what people want.Â Keywords: Branding and Promotion, Marketing Communication, Social Media, Social Media strategy.